2010
DOI: 10.1111/j.1532-5415.2010.03002.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assessment of Older Adults With Chronic Obstructive Pulmonary Disease Living at Home

Abstract: HospitalizationsThe risk of rehospitalization in the TG was 40% lower (P 5.03) than in the CG. The ratio of the risk of rehospitalization, after the Di.Pro.Di and before, was 0.30 (P 5.009). Length of StayThe duration of hospital stay was 10.4 days shorter in the TG (Po.001) than in the CG. The duration of hospital stay was in the TG was 11.9 days shorter after the Di.Pro.Di than before (Po.001). CONCLUSIONDi.Pro.Di significantly reduced number of rehospitalizations and hospital length of stay. A possible reas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
(5 reference statements)
1
0
0
Order By: Relevance
“…These results are consistent with a study by Xiang et al 15 ) , who reported that patients with COPD who participated a respiration rehabilitation program (including medical and psychological interventions) improved their instrumental activities of daily living in areas such as telephone use, shopping, public facility use, and financial management. Our results are also consistent with those of a previous study by Merida et al 16 ) , who reported that 25 patients with COPD who participated in a respiration rehabilitation program involving daily living exercise for 4 weeks, to improve respiration functions, showed improvements in their scores for instrumental activities of daily living after the intervention.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with a study by Xiang et al 15 ) , who reported that patients with COPD who participated a respiration rehabilitation program (including medical and psychological interventions) improved their instrumental activities of daily living in areas such as telephone use, shopping, public facility use, and financial management. Our results are also consistent with those of a previous study by Merida et al 16 ) , who reported that 25 patients with COPD who participated in a respiration rehabilitation program involving daily living exercise for 4 weeks, to improve respiration functions, showed improvements in their scores for instrumental activities of daily living after the intervention.…”
Section: Discussionsupporting
confidence: 93%